TCP24 modulates secondary cell wall thickening and anther endothecium development - Wang, Han; Mao, Yanfei; Yang, Jun; He, Yuke (Frontiers in Plant Science, 2015)
miR319-targeted TCP genes are believed to regulate cell division in leaves and floral organs. However, it remains unknown whether these genes are involved in cell wall development. Here, we report that TCP24 negatively regulates secondary wall thickening in floral organs and roots. The overexpression of the miR319a-resistant version of TCP24 in Arabidopsis disrupted the thickening of secondary cell walls in the anther endothecium, leading to male sterility because of arrested anther dehiscence and pollen release. Several genes linked to secondary cell wall biogenesis and thickening were down-regulated in these transgenic plants. By contrast, the inhibition of TCP24 using the ectopic expression of a TCP24-SRDX repressor fusion protein, or the silencing of TCP genes by miR319a overexpression, increased cell wall lignification and the enhanced secondary cell wall thickening. Our results suggest that TCP24 acts as an important regulator of secondary cell wall thickening and modulates anther endothecium development.